INTEGRATED MARKETING COMMUNICATION (IMC) STRATEGIES AT SHARIA SYAFAAT MARCOMM DIGITAL AGENCY IN YOGYAKARTA IN 2021 - Ula Ulhusna; Siti Latifah Mubasiroh (Universitas Islam Indonesia, 2023)
Integrated Marketing Communicationplay a key role in managing marketing strategies. IMC itself focuses on marketing its product, services and facilities to gain good public opinion and maintance a positive image.the purpose of this study is to describe the work system of IMC at sharia Syafaat Marcomm Digital Agency itself. The constructivist paradigm is the mainstay of this research because the truth of reality which is seen as a result of social construction and the truth of realyty are relative. This is support by a target sampling technique, namely looking for relevant informants such as directors and general managers to ensure the data obtained are valid. This study use qualitative research, which describes the problem under study obtained through interviews with interview tehniques, observation and collection of documentation. Syafaat Marcomm uses IMC such as advertising, Consumer Sales Promotion, Trade Sales Promotion, Public Relation, and Publications, Sponsorship and Event, Direct Marketing in serving clients and applaying to clients. In accordance with thw vision and mission of improving product quality and quality to develop following technological civilization and becoming a creative company in every information technology service.